Employee Performance Analysis of Employee Engagement, Resilience, Career Development and Competence - Supardi, Supardi; Utama, Doni Putra (Indonesian Journal of Business Analytics, 2023)
The purpose of this research is to review previous articles, looking for relationships between variables. This research is a literature review study that does not use data processing and there is no research sample. The findings of this study are that there is a relationship between variables seen from previous research that supports the literature review of this article, the novelty of this article is that no one has examined all the independent variables on the dependent. The number of significant articles makes the article a reference for further research and is developed quantitatively.